Stay or go? Changing breeding conditions affect sexual difference in colony attendance strategies of Atlantic puffins Fratercula arctica - Tycho Anker‐Nilssen; Martina Kadin; Christoffer Høyvik Hilde (Ecology and Evolution)
Abstract Male and female birds have different roles in reproduction and, thereby in their reproductive investment, which in turn may increase negative effects of poorer breeding conditions caused by e.g., climate change or ecosystem regime shifts. By using a 33‐year time series of resightings of Atlantic puffins Fratercula arctica individually colour‐ringed as breeders in previous years, we showed that the difference in colony attendance of male and female birds depended on the environmental conditions for raising young, proxied by the average duration of the chick period and size of the herring Clupea harengus fed to the chicks in the colony each year. The longer the chick period, the more was the sex ratio of adults sitting visibly in the colony biased in favour of males. An increase in herring size, indicating better feeding conditions for raising chicks, led to more observations of both sexes. Additionally, we found that birds were observed less with age and females more so than males. We discuss the results in relation to general life‐history theory on sexual differences in trade‐offs between individual investment in breeding and own survival. Our results suggest that females are increasingly more willing than males to invest in provisioning for the chick the more and longer the chick needs such care.